Rifampin-resistance-associated mutations in the rifampin-resistance-determining region of the rpoB gene of Mycobacterium tuberculosis clinical isolates in Shanghai, PR China. Issue 3 (28th March 2021) - Guo, Yinjuan; Cao, Xingwei; Yang, Jinghui; Wu, Xiaocui; Liu, Yin; Wan, Baoshan; Hu, Longhua; Wang, Hongxiu; Yu, Fangyou
Abstract : Introduction. Resistance to rifampin (RIF) in Mycobacterium tuberculosis infection is associated with mutations in the rpoB gene coding for the β-subunit of RNA polymerase. The contribution of various rpoB mutations to the development and level of RIF resistance remains elusive. Hypothesis/Gap Statement. Various rpoB mutations may be associated with differential levels of RIF resistance. Aim. This study aimed to investigate the relationship between specific rpoB mutations and the MICs of RIF and rifabutin (RFB) against M. tuberculosis . Methodology. Of the 195 clinical isolates, 105 and 90 isolates were randomly selected from isolates resistant to RIF and sensitive to RIF, respectively. The MICs of 12 agents for M. tuberculosis isolates were determined using commercial Sensititre M. tuberculosis MIC plates and the broth microdilution method. Strains were screened for rpoB mutations by DNA extraction, rpoB gene amplification and DNA sequence analysis. Results. One hundred isolates (95.24 %) were found to have mutations in the RIF-resistance-determining region (RRDR) of the rpoB gene. Three rpoB mutations were identified in 90 RIF-susceptible isolates. Out of 105 isolates, 86 (81.90 %) were cross-resistant to both RIF and RFB. The most frequent mutation occurred at codons 450 and 445. We also found a novel nine-nucleotide (ATCATGCAT) deletion (between positions 1543 and 1551) in the rpoB gene in two strains (1.90 %) with resistance to RIF, but susceptibility to RFB. In addition, the mutation frequency at codon 450 was significantly higher in RIF-resistant/RFB-resistant (RIF R /RFB R ) strains than in RIF R /RFB S strains (75.58 % versus 21.05 %, P <0.01), whereas the mutation frequency at codon 435 was significantly lower in RIF R /RFB R strains than in RIF R /RFB S strains (1.16 % versus 26.32 %, P <0.01). Conclusion. Our data support previous findings, which reported that various rpoB mutations are associated with differential levels of RIF resistance. The specific mutations in the rpoB gene in RIF R /RFB R isolates differed from those in the RIF R /RFB S isolates. A novel deletion mutation in the RRDR might be associated with resistance to RIF, but not to RFB. Further clinical studies are required to investigate the efficacy of RFB in the treatment of infections caused by M. tuberculosis strains harbouring these mutations.